2015
DOI: 10.1186/s12885-015-1431-6
|View full text |Cite
|
Sign up to set email alerts
|

BCG+MMC trial: adding mitomycin C to BCG as adjuvant intravesical therapy for high-risk, non-muscle-invasive bladder cancer: a randomised phase III trial (ANZUP 1301)

Abstract: BackgroundDespite adequate trans-urethral resection of the bladder tumour (TURBT), non-muscle-invasive bladder cancer (NMIBC) is associated with high rates of recurrence and progression. Instillation of Bacillus Calmette-Guérin (BCG) into the urinary bladder after TURBT (adjuvant intravesical administration) reduces the risk of both recurrence and progression, and this is therefore the standard of care for high-risk tumours. However, over 30 % of people still recur or progress despite optimal delivery of BCG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…[12] While intravesical BCG therapy is superior to MMC therapy in reducing rate of recurrence and tumor progression, a phase II trial has found the combination of MMC with BCG to be better than BCG therapy alone in improving recurrence-rates (42% vs. 58%). [13] The on-going phase III trial is evaluating the efficacy of the MMC and BCG combination intravesical therapy in high-risk NMIBC patients by assessing the disease free survival over 5 years.…”
Section: Bcg-naïvementioning
confidence: 99%
“…[12] While intravesical BCG therapy is superior to MMC therapy in reducing rate of recurrence and tumor progression, a phase II trial has found the combination of MMC with BCG to be better than BCG therapy alone in improving recurrence-rates (42% vs. 58%). [13] The on-going phase III trial is evaluating the efficacy of the MMC and BCG combination intravesical therapy in high-risk NMIBC patients by assessing the disease free survival over 5 years.…”
Section: Bcg-naïvementioning
confidence: 99%
“…Fluoroquinolones may reduce the occurrence of moderate or severe toxicity [29]. Newer techniques under investigation to evaluate efficacy and toxicity include the addition of mitomycin C to BCG as adjuvant intravesical therapy [30]. Currently however, there is no effective preventative method for BCG toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The BCG + Mitomycin trial (ACTRN12613000513718; http://ClinicalTrials.gov NCT02948543; ANZUP 1301) is an ongoing randomized phase III trial, aiming to compare the efficacy and safety of the addition of intravesical mitomycin chemotherapy to standard intravesical BCG in patients with resected, high‐risk non‐muscle‐invasive bladder cancer (NMIBC) . Our meta‐analysis suggested reduced rates of recurrence (relative risk 0.75; 95% CI 0.61–0.92; P < 0.01) and progression (relative risk 0.45; 95% CI 0.25–0.81; P < 0.01) with combination treatment as compared to treatment with BCG alone in patients with Ta or T1 disease, but not in those with pure carcinoma in situ (CIS) ; however, this remains unproven for all subgroups of high‐risk NMIBC, or when treatment is delivered without electromotive delivery (as is usual), and requires corroboration in a definitive, large‐scale, randomized phase III trial.…”
Section: Trial Overviewmentioning
confidence: 94%